Does fire affect the temporal pattern of trophic resource supply to pollinators and seed-dispersing frugivores in a Brazilian savanna community? - Tunes, Priscila [UNESP] (2017)
In tropical savannas, such as the campo cerrado in Brazil, fire plays an important role, affecting plant species’ life history. Since fire has the potential to modify the structure of savanna communities as a whole, it is expected that it may influence the resource supply for mutualists by altering the pattern of investment in sexual reproduction. We used an experimental approach to test if fire alters trophic resource availability to pollinators (nectar, pollen, and oil) and seed-dispersing frugivores (fleshy fruits) by altering the seasonality of reproductive phenophases in a savanna community. We sampled all individuals of 60 species that were common to both control and experimental fire treatments. Each month we recorded the number of reproductive individuals to test whether fire affected the temporal resource offered by the plant assemblage as a whole, and by each specific plant group supporting distinct groups of pollinators and seed-dispersing frugivores. We noticed that fire advanced the nectar, pollen, and fleshy fruit offered by the whole assemblage. Additionally, fire affected the temporal pattern of nectar and pollen available to various pollinator groups, and of fleshy fruits available to all seed-dispersing frugivores. In general, fire seems to have a neutral or even a positive effect on resource availability to mutualists. Nevertheless, there were differences in the availability of the resource utilized by each guild of mutualists.